An exploratory study on the teaching and learning of TOEIC listening skill at a university in HaNoi - Nguyễn, Thu Trang (University of Languages and International Studies, 2017)
This study has been conducted to explore the teaching and learning of TOEIC listening skill at Hanoi Law University. The subjects of the study are 50 students and 14 English lecturers at Hanoi Law University. The data have been collected via questionnaires (...)